Australia in the Great War - Payton, Philip (Robert Hale, 2015)
Australia in the Great War is a compelling history of Australia and its people during the global conflict of 1914-1918. It charts the experiences of ordinary men and women against a backdrop of momentous events on the international stage, and shows how war helped shape an emerging Australian national identity.